Peningkatan Kesuburan Tanah Dan Produktivitas Sebagai Hasil Pengolahan Lahan Di Dusun Ngadilegi, Pandaan - Fiorentina Cahaya Rizki; Pranadipa Ramadhan Wicaksono; Fitri Wijayanti (Jurnal Informasi Pengabdian Masyarakat, 2024)
Optimal soil fertility is the main key in achieving sustainable agricultural productivity. This abstract describes various efforts and strategies that can be adopted to improve soil fertility and, as a result, increase agricultural productivity. Increasing soil fertility not only increases agricultural yields, but can also contribute to global food security, reduce degraded land, and support environmental sustainability. This abstract aims to provide insight into various strategies that can be adopted to increase soil fertility and agricultural productivity. With a deep understanding of soil dynamics and a science-based approach, stakeholders can develop agricultural policies and practices that support sustainable agricultural growth.